The impact of shared domain knowledge (SDK) on strategic information systems planning (SISP) and effectiveness - Hiralall, Simla (Department of Information Systems, 2024)
In today's competitive business environment, organisations are increasingly dependent on Information Technology (IT) to support and enhance their business processes. In some organisations, IT does not merely support the business - it is the business - as IT forms the basis for the entire business model. IT has become a strategic asset and a key business enabler in organisations yet failures in IT investment are still attributed to the technology rather than its links with business operations, customer value, and management decision making. This could be attributed to a lack of alignment or harmony between IT and business imperatives within organisations. Strategic Information Systems Planning (SISP) is the planning process of coordinating the relationship between IT and the business and alignment is viewed as the result of this process. Shared Domain Knowledge (SDK) is a factor that has been identified as being very important in influencing alignment, IT decision processes, IT-line partnerships, IT performance, and IT use. To examine the impact of SDK on SISP and effectiveness (measured by alignment between IT and business), this study posits that SDK positively influences SISP effectiveness. Data, which was gathered from consultants in a large, global IT organisation, through the use of a structured questionnaire, was analysed and the finding was that there was support for SDK positively influencing SISP effectiveness. Additional findings of this study were that the SISP process dimensions of rationality and IT manager's participation in business planning positively influenced intellectual alignment and social alignment respectively and SDK positively influenced all of the SISP process dimensions (rationality, adaptation, BP/ISP integration, and IT manager's participation in business planning) examined in this study. SDK was also found to positively impact social alignment, intellectual alignment, and consequently SISP effectiveness.